2014
DOI: 10.3906/sag-1211-39
|View full text |Cite
|
Sign up to set email alerts
|

Folate and homocysteine metabolisms and their roles in the biochemical basis of neuropsychiatry

Abstract: This work aims to study recent climatic oscillations and their influence on sedimentation in the Ria de Vigo, a coastal embayment in Galicia, NW Spain. It is based on the study of clay mineral assemblages, in conjunction with other proxies (granulometric, geochemical, geochronological and microfaunal), in the core KSGX 24. A Benthic Foraminifera High Productivity (BFHP) proxy was used to determine changes in the flux of organic matter (OM) at the bottom of the study area. Total organic carbon (TOC) content is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 117 publications
1
27
0
1
Order By: Relevance
“…515 Consistent with this, alterations in methylation-dependent processes are associated with cancer, 16 neurodegenerative/neuropsychiatric disorders, 1719 inflammation, 20,21 metabolic disorders, 22 fundamental development/regenerative medicine, 23,24 susceptibility to disease/adverse drug response, 25,26 and drug resistance. 1315,27,28 While there have been great advances in methylation-dependent bioinformatics and disease-associated biomarkers, 2931 the study of intracellular MT spatial/temporal resolution, specificity, and/or function remains a challenge.…”
mentioning
confidence: 60%
“…515 Consistent with this, alterations in methylation-dependent processes are associated with cancer, 16 neurodegenerative/neuropsychiatric disorders, 1719 inflammation, 20,21 metabolic disorders, 22 fundamental development/regenerative medicine, 23,24 susceptibility to disease/adverse drug response, 25,26 and drug resistance. 1315,27,28 While there have been great advances in methylation-dependent bioinformatics and disease-associated biomarkers, 2931 the study of intracellular MT spatial/temporal resolution, specificity, and/or function remains a challenge.…”
mentioning
confidence: 60%
“…HCy is also important for the synthesis of some amino acids and polypeptides, such as cystathionine, cysteine, and glutathione. Some neuropsychiatric disorders have been related to abnormalities of the one‐carbon metabolic pathway . One proposed mechanism is that autistic children have lower levels of glutathione, while having elevated levels of HCy and S‐adenosylhomocysteine, which are indicative of oxidative stress, and a poorer ability to eliminate heavy metal, such as mercury …”
Section: Future Directionsmentioning
confidence: 99%
“…Some neuropsychiatric disorders have been related to abnormalities of the one-carbon metabolic pathway. 121 One proposed mechanism is that autistic children have lower levels of glutathione, while having elevated levels of HCy and S-adenosylhomocysteine, which are indicative of oxidative stress, and a poorer ability to eliminate heavy metal, such as mercury. 122 Since a study of 35 ASD children and age-and sex-matched controls showed that the dietary choline and betaine as well as their plasma choline and betaine levels were lower than that of controls, 123 it was thought that it could be possible to supplement these children with choline and betaine for alleviating their high HCy levels.…”
Section: Potential Treatment or Preventive Strategies For Autismmentioning
confidence: 99%
“…However, the most important disease group, which is associated with FA deficiency and hyperhomocysteinemia, is neurological and psychiatric diseases. In recent years, there have been a number of publications that FA is associated with diseases such as Parkinson's, MS, Alzheimer, stroke, anxiety disorders, depression, schizophrenia, bipolar disorder, congenital neural tube defects [14][15][16]. High levels of Hcy are toxic to neural cells therefore Hcy contributes to the pathogenesis of neurodegenerative disorders.…”
Section: The Impacts Of Hcy Fa and Vitb12mentioning
confidence: 99%